THE RESPONSIBILITY OF INTERNATIONAL ORGANISATION ON ENVIRONMENTAL DAMAGE DURING AN ARMED CONFLICT (Case Study of NATO Air Campaign against Kosovo in 1999) - Dessy Maeyangsari (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
The role of international organisations within international peacekeeping and enforcements nowadays are increasingly high.Nevertheless, the provisions regarding their action andaccountability entailed behind have not been settled yet byinternational law. Such concerning case is the involvement ofNATO during Kosovo Conflict in 1999 where NATO conducted aircampaign for 72 days. The targets of attacks are industrialfacilities, oil refineries and other public infrastructure. The impactof the aerial bombardment caused the spilling tons of oil into riversin Kosovo and some burned, causing severe air pollution overseveral times. Moreover, there is another issue of the use ofDepleted Uranium during this armed conflict. These significantenvironmental impacts as the result of NATO's air strikes are not inaccordance with the provisions and principles of internationalhumanitarian law as well as the environmental law. However, dueto the lack of an international legal instrument regulatinginternational organisations responsibility for environmentaldamage during an armed conflict; in practice, it is not easy to claimthe responsibility of international organisation.Keyword: Responsibility, Kosovo, NATO, armed conflict,environmental damage